Analisis Yuridis Keabsahan Akta Sewa Menyewa Yang Direnvoi Secara Sepihak (Studi Putusan Nomor 146/PDT/2018/PT.Bdg) - Tri Wahyuni Limbong (Iuris Studia: Jurnal Kajian Hukum, 2021)
One of the deed of agreement made by a Notary is a deed of lease agreement, namely: an agreement, whereby one party binds himself to provide enjoyment of an item to another party for a certain time, with payment of a price agreed by the latter party. This research is descriptive analysis. Descriptive means being able to provide a clear and systematic description of the problem to be studied. Analysis means analyzing carefully the problem based on the picture and facts so as to be able to answer the problems related to this research. The validity of the lease deed which is renvoied or changed unilaterally by the Notary causes losses to the parties as well as to other parties. Mistakes made by this Notary can result in a rental deed which is changed unilaterally to become null and void (van rechtswege nietig), can be canceled (vernietigbaar), or only has proving power as an underhand deed (onderhands act). The Notary's responsibility for the validity of the lease deed which is renvoied or changed unilaterally is referring to Article 65A UUJN, Article 1869 of the Civil Code and can also be held criminally responsible for the Notary, namely the Notary can be punished criminally, if it can be proven in court, that the Notary intentionally together with the parties/appearers to make a deed with the intent and purpose of benefiting only certain parties or appearers or harming other parties. The decision of the Panel of Judges on case number 146/PDT/2018/PT. It was felt that Bdg had not given justice to the Plaintiff because the violation of the regulations regarding changes to the contents of the deed or renvoi resulted in the deed only having evidentiary power as an underhand deed and could be used as an excuse for the parties to demand reimbursement of costs, compensation, and interest from a Notary